PENERAPAN ASAS NASIONALITAS DALAM PERUNDANG-UNDANGAN AGRARIA INDONESIA (STUDI KASUS PP NO.40 TAHUN 1996) - Jum Anggriani (Jurnal Dinamika Hukum, 2012)
The Agrarian law regulated that only the Indonesian citizen that have the complete connection with the earth, water and the sky. This means that only Indonesian citizen that have “the rightful autority of land”. This suggests there are a principle of nationality in the Law no. 5 years 1960 primarily as the strongest and fullest of a hereditary property. Keywords : nationality principle, public service, welfare state.